1985
DOI: 10.1126/science.3865369
|View full text |Cite
|
Sign up to set email alerts
|

A Transgenic Mouse Model of the Chronic Hepatitis B Surface Antigen Carrier State

Abstract: In an attempt to establish a model of the healthy carrier state in hepatitis B virus (HBV) infections, transgenic mice expressing HBV genes were produced. Fertilized one-cell eggs were microinjected with subgenomic fragments of HBV DNA containing the coding regions for the HBV surface antigen (HBsAg) and pre-S and X antigens. Either the normal (HBV) or metallothionein promoters were used to obtain expression of the HBV genes. There was no evidence of viral replication or tissue pathology. The integrated HBV DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
204
1
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(215 citation statements)
references
References 19 publications
6
204
1
4
Order By: Relevance
“…HBsAg transgenic mice C57BL/6J-TgN (AlblHBV) 44Bri (named as HBs-B6 mice in this study) were used, which express HBsAg in serum, liver and kidney tissues to mimic human healthy chronic HBsAg carriers [24,25]. Eight-to 10-week-old male HBs-B6 mice were obtained from VITALRIVER Experiment Animal Company (Beijing) which purchased them from Jackson Lab and bred them for us.…”
Section: Micementioning
confidence: 99%
See 1 more Smart Citation
“…HBsAg transgenic mice C57BL/6J-TgN (AlblHBV) 44Bri (named as HBs-B6 mice in this study) were used, which express HBsAg in serum, liver and kidney tissues to mimic human healthy chronic HBsAg carriers [24,25]. Eight-to 10-week-old male HBs-B6 mice were obtained from VITALRIVER Experiment Animal Company (Beijing) which purchased them from Jackson Lab and bred them for us.…”
Section: Micementioning
confidence: 99%
“…In this study, hepatitis B surface antigen (HBsAg) transgenic mice, which mimic human healthy chronic HBsAg carriers [24,25], were triggered by a synthetic dsRNA analogue Poly(I:C), a ligand of toll-like receptor 3 (TLR3) and also a well-known potent activator for NK cells [13,14,26]. In our previous study, injection of Poly(I:C) could preferentially recruit and activate NK cells in liver and induce mild liver injury in wild mice [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Because HBV does not infect such animals, we decided to produce HBV transgenic mice to achieve this objective. 43 Initially, we showed that mice that express HBV envelope proteins in their hepatocytes develop acute viral hepatitis after adoptive transfer of CD8-positive, MHC class I restricted, envelope (HBsAg)-specific CTL lines and clones. 44,45 Furthermore, we showed that the disease progresses through an orderly series of clearly definable steps.…”
Section: Ctl-induced Liver Disease In Hbv Transgenic Micementioning
confidence: 99%
“…[1][2][3][4][5] During the first months of life, the hepatic damage consists of degenerative alterations. 2 Later, an active inflammatory response commences that induces a marked damage-related compensatory proliferative reaction.…”
mentioning
confidence: 99%